2013
DOI: 10.1590/s0100-736x2013001300010
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative metabolism and muscle biochemical profile of polo horses supplemented with an ADE vitamin complex

Abstract: Pesq. Vet. Bras. 33(Supl.1):58-62, dezembro 2013 58 RESUMO.-[Metabolismo oxidativo e perfil bioquími-co muscular de cavalos de pólo suplementados com complexo vitamínico ADE.] O jogo de pólo se caracteriza por mudanças abruptas e frequentes na intensidade do exercício dos cavalos. Para satisfazer esta demanda inconstante de energia, os animais utilizam as vias aeróbia e anaeróbia em proporções e intensidade variáveis. Neste contexto deve haver equilíbrio entre a formação das espé-cies reativas de oxigênio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…It was found that supplementation with the ADE vitamin complex in a dose of 1 mL/50 kg of live weight (270,000 IU of vitamin A, 80,000 IU of vitamin D, and 80 IU of vitamin E/mL) via intramuscular injection can make muscle metabolism more efficient during exercise, suggesting a possible therapeutic approach [ 59 ]. After the game, the polo horses in the treated group had higher AST, lactate, and glucose levels than the horses in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that supplementation with the ADE vitamin complex in a dose of 1 mL/50 kg of live weight (270,000 IU of vitamin A, 80,000 IU of vitamin D, and 80 IU of vitamin E/mL) via intramuscular injection can make muscle metabolism more efficient during exercise, suggesting a possible therapeutic approach [ 59 ]. After the game, the polo horses in the treated group had higher AST, lactate, and glucose levels than the horses in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the treated animals used their energy more efficiently. Before the game, the animals in the treated group also had higher GSH levels and lower lactate levels, indicating a better anti-oxidant supply [ 59 ].…”
Section: Resultsmentioning
confidence: 99%